A novel library of saccharin and acesulfame derivatives as potent and selective inhibitors of carbonic anhydrase IX and XII isoforms. Issue 5 (1st March 2016) - Carradori, Simone; Secci, Daniela; De Monte, Celeste; Mollica, Adriano; Ceruso, Mariangela; Akdemir, Atilla; Sobolev, Anatoly P.; Codispoti, Rossella; De Cosmi, Federica; Guglielmi, Paolo; Supuran, Claudiu T.
Graphical abstract: Abstract: Small libraries of N -substituted saccharin and N -/ O -substituted acesulfame derivatives were synthesized and tested as atypical and selective inhibitors of four different isoforms of human carbonic anhydrase (hCA I, II, IX and XII, EC 4.2.1.1). Most of them inhibited hCA XII in the low nanomolar range, hCA IX with K I s ranging between 19 and 2482 nM, whereas they were poorly active against hCA II ( K I s >10 μM) and hCA I ( K I s ranging between 318 nM and 50 μM). Since hCA I and II are ubiquitous off-target isoforms, whereas the cancer-related isoforms hCA IX and XII were recently validated as drug targets, these results represent an encouraging achievement in the development of new anticancer candidates. Moreover, the lack of a classical zinc binding group in the structure of these inhibitors opens innovative, yet unexplored scenarios for different mechanisms of inhibition that could explain the high inhibitory selectivity. A computational approach has been carried out to further rationalize the biological data and to characterize the binding mode of some of these inhibitors.